The role of physical activity in the clinical outcomes of people diagnosed with Covid-19: A systematic review - Euripedes Barsanulfo Gonçalves Gomide; Pedro Pugliesi Abdalla; Marcel Frezza Pisa; Guilherme Schneider; Leticia Genova Vieira; Lisa Fernanda Mazzonetto; Alcivandro de Sousa Oliveira; Emerson Sebastião; André Pereira dos Santos (Elsevier, 2022)
Objective: This review aimed to compile the evidence on PA and clinical outcomes of people receiving a positive diagnosis of covid-19. Design: Systematic review. Methods: The search was performed in five databases: EMBASE, MEDLINE via PubMed portal, Scopus, SPORTDiscus via EBSCO platform, and Web of Science. In addition, the "gray" literature was searched through Google Scholar and medRxiv published between January 2020 and July 2022. Studies were assessed for risk of bias, with the extraction of relevant data. Our search revealed a total of 10,028 studies. Results: After applying the eligibility criteria 32 studies were included. Thirty-one studies were at low to moderate risk of bias. Physically active individuals, who were diagnosed with covid-19, presented attenuation of clinical outcomes, such as decreased risk of hospitalization, recovery time, number of symptoms, severity, and ICU and death when compared to individuals with low levels of PA or classified as sedentary. Conclusions: Physically active individuals when diagnosed with covid-19 may have decreased risk of several clinical outcomes related to covid-19, including but not limited to hospitalization and number of symptoms. Public health authorities should develop strategies and initiatives that promote safe PA environments to improve the clinical prognosis of people diagnosed with covid-19. Study registration: Open Science Framework (OSF), DOI registry 10.17605/OSF.IO/PV6NF. It can be consulted through the access link: https://doi.org/10.17605/OSF.IO/PV6NF, October 07, 2021.